Abrupt climate variability since the last deglaciation based on a high-resolution peat dust deposition record from southwest China. (15th January 2021) - Peng, Haijun; Bao, Kunshan; Yuan, Lingui; Uchida, Masao; Cai, Cheng; Zhu, Yongxuan; Hong, Bing; Guo, Qian; Ding, Hanwei; Yao, Hu; Hong, Yetang
Abstract: The mechanism of abrupt climate changes in east Asia since the last deglaciation remains poorly explored due to the low number of high-resolution geological archives. Here we present a major and trace element including rare-earth elements (REEs) analysis of a 6 m peat archive from the Hengduan Mountains to reconstruct the rapid changes in monsoonal climate since the last deglaciation. The physicochemical parameters and Ca/Mg ratio illustrated the ombrotrophic characterization of the Yuexi peat core over the last 8800 years. Abrupt increases in dust fluxes were identified during the Old Dryas (OD), the Younger Dryas (YD), and the 4.2 kyr cold event periods. The mineral dust flux remained quite stable and low during the middle Holocene. The lowest average dust deposition rate between 8800 and 5000 cal yr BP represents a baseline of long-term atmospheric dust flux in China. The Y/ΣREE, La/Yb, Y/Yb, Y/Er indicate that deserts in northwest China, the Loess Plateau, and Tibetan soils were the dominant dust sources to the Yuexi peatland. The comparison with global climatic records suggested a teleconnection between the climate change in southwest China and North Atlantic cooling events, which implies that the abrupt variation in dust fluxes was linked with Asian monsoons variations. Our results also reveal that increased human activities significantly contribute to the dust fluxes during the late Holocene. Highlights: A 6-m peat geochemical record from southwest China documented the rapid monsoonal changes since the last deglaciation. REEs tracers indicated the dust to the peatland sourced from northwest China deserts, the Loess Plateau, and Tibetan soils. Abrupt increases in dust fluxes were identified during the Old Dryas, the Younger Dryas, and the 4.2-kyr event periods. Increased human activities significantly contribute to the dust fluxes during the late Holocene.